Large shareholder diversification and corporate risk-taking - Mara Faccio; Maria-Teresa Marchica; Roberto Mura (The University of Manchester, Manchester Business School, 2011)
Using new data for the universe of firms covered in Amadeus, we reconstruct the portfolios of shareholders who hold equity stakes in private and publicly-traded European firms. We find great heterogeneity in the degree of portfolio diversification across large shareholders. Exploiting this heterogeneity, we document that firms controlled by diversified large shareholders undertake riskier investments than firms controlled by non-diversified large shareholders. The impact of large shareholder diversification on corporate risk-taking is both economically and statistically significant. Our results have important implications at the policy level because they identify one channel through which policy changes can improve economic welfare.
Keywords: G11; G15; G31; 330; Risk-taking choices; Large shareholders; Portfolio diversification